Correlation between acute stroke-induced white matter lesions and insulin resistance. Issue 11 (March 2018) - You, Cheng-jin; Liu, Dan; Liu, Li-li; Li, Guo-zhong
Abstract : Abstract: The present study was to examine the relationship between white matter lesions (WMLs) and insulin resistance (IR) in patients with acute stroke and evaluate clinical prognosis. Around 200 patients with initial onset of acute stroke including 146 patients (73.0%) with WMLs and 54 patients (27%) without WMLs were analyzed by neuropsychological scales. Fasting blood glucose (FBG), fasting insulin, blood lipid, homocysteine (Hcy), high-sensitivity C-reactive protein (hs-CRP), creatinine, and uric acid, diabetes mellitus (DM), prediabetes (PD), and normal glucose (NG) were determined according to HbA1c levels. According to homeostasis model assessment (HOMA)-IR index of IR, HOMA-IR index ≥2.5 indicated IR, and HOMA-IR index < 2.5 represented noninsulin resistance (NON-IR). IR values and the proportion of patients with IR, HbA1c levels and the quantity of DM patients, the levels of low-density lipoprotein cholesterol, Hcy, and hs-CRP of patients with WMLs were significantly higher than those in patients without WMLs (all P < .05). OR value of IR exposure and WMLs was 1.862 (1.235–2.236). OR values of level 1, level 2, and level 3 WMLs were 1.632 (1.032–2.532), 1.328 (1.152–2.865), and 1.158 (0.639–3.526), respectively. Regarding WMLs patients, MoCA and MMSE scores were significantly decreased, and Hamilton Depression Scale scores were significantly increased (all P < .05). National Institutes of Health Stroke Scale and modified Rankin scale scores of patients with WMLs were significantly increased, and BI scores were significantly decreased (all P < .05). IR is intimately correlated with the WMLs of acute stroke. The incidence and severity of WMLs are significantly associated with cerebral arterial thrombosis, neuropsychology, and neurological scores.